Complementarity of the Social and Economic Policy of the State: Theoretical and Applied Aspects and Modern Tendencies - Ventsel , Viktor (Pressing Problems of Public Administration, 2019)
Among the most important aspects of the existence of the human community are social factors that are crucial for the formation of political and economic systems, and also in uence the formation of moral, humanitarian, ethical, spiritual, aesthetic and other universal values. The rapid global development of human civilization has led to the problem of adaptation of humanity to existence in the modern technological world, since there are currently no philosophical and humanitarian models that would be adequate to the modern world order and would provide clear moral and ethical guidelines and algorithms for action. According to modern philosophers today, we are witnessing the birth of a new revolutionary civilization, which challenges the old established traditions. In this context, attention should be paid to the economic aspects of the present. The modern market economic system was formed at the time when the urgent issues were the development of industrial production, ensuring the ever-increasing material needs of people. The serious disadvantage of the economic systems thus formed is that they are based on permanent expanded growth. However, unlimited economic growth is impossible because the aggravation of economic, environmental and social crises is a logical result, and despite modern knowledge, mankind is not able to cope with these challenges. In the context of modern revolutionary transformations of social life, social policy must play a leading role in the development and the existence of a modern state, creating comfortable conditions for the life of a modern person. Social policy is closely interrelated with the economic potential of the state, and also conditioned to its historical and cultural development. In view of the speci c aspects of development, each country forms and implements a social policy that is unique to it. In world practice, there are several approaches to the classi cation of social policy models. In particular, it is considered that the Bismarckian and Beveridge models of social policy have been elaborated and developed within the European Union. Also widely used is the classi cation of types of the states, proposed by Danish sociologist G. Esping-Andersen. Scientist distinguish three cluster types of such the states: liberal, corporatist, social democratic. In the process of social and economic development, new social relations and new social needs are emerging, including the need to  nd new and improve existing models of social policy of the state. Ukraine continues to form its statehood and the main strategic vector of development is determined by the European integration course. At this stage, the most pressing issue is the formation of an effective social policy that should be based on the existing theoretical basis and empirical experience of other countries. The primary tasks of state bodies of Ukraine should be: de nition of the dominant model of social policy and development of a strategy for its implementation; inventory of social protection programs on the subject of their relevance and the possibility of adequate  nancial support; strengthening the role of the state in the period of reforming the economic and social spheres in order to ensure organizational orderliness and manageability of these processes.